Unusual spectroscopic and photophysical properties of meso-tert-butylBODIPY in comparison to related alkylated BODIPY dyes. Issue 109 (20th October 2015) - Jiao, Lijuan; Yu, Changjiang; Wang, Jun; Briggs, Edward A.; Besley, Nicholas A.; Robinson, David; Ruedas-Rama, María J.; Orte, Angel; Crovetto, Luis; Talavera, Eva M.; Alvarez-Pez, Jose M.; Van der Auweraer, Mark; et al.
Abstract : meso-t -Bu-BODIPY produces unusual spectroscopic and photophysical characteristics in comparison to those of related alkylated BODIPY dyes. Abstract : Five alkyl-substituted difluoroboron dipyrrin (BODIPY) dyes have been synthesized: three with a methyl, isopropyl or tert -butyl group at the meso -position of the BODIPY core and two substituted with one or two tert -butyl functions at the 3/5-positions. X-Ray structural analysis, UV-vis absorption spectroscopy and fluorescence (steady-state and time-resolved) techniques have been used to study the structures and the spectroscopic/photophysical properties of these dyes. All but one of these BODIPYs are highly fluorescent in all the solvents tested, the exception being meso-tert -butylBODIPY (2 ). Derivative2 differs from the other alkylated boron dipyrrins as it exhibits a broad and red-shifted fluorescence band with a large Stokes shift. In addition, very low fluorescence quantum yields and short fluorescence lifetimes characterize2 . Quantum chemical calculations indicate that2 has a distorted, nonplanar geometry in the S1 excited state due to the rotation of 8- tert -butyl group. Our results lead us to the conclusion that the torsional rotation about the bond connecting the meso -C and the quarternary C of the tert -butyl group of2 plays a crucial role in the fast radiationless deactivation of this isomer.